Attention Bias for Threatening Information in Children Following a Distressing Medical Procedure. (August 2014) - Nixon, Reginald David Vandervord; Brewer, Neil; McKinnon, Anna Catherine; Cameron, Kate; Bray, Jemma
<x xml:space="preserve">Abstract</x> Attention bias is common in adults with post‐traumatic stress disorder (PTSD) but is less studied in children. Children (n = 22) who experienced a potentially distressing procedure in an outpatient clinic (removal of K‐wires from orthopaedic fractures) and a group of medically unwell children (illness group; n = 27) were compared with healthy controls (n = 32). Children's baseline level of PTS symptoms were indexed prior to the medical procedure, and again at 1‐week follow‐up. Immediately after the K‐wire removal, children completed a dot probe task using two categories of target words (medical threatening and emotionally threatening). While K‐wire children showed an overall bias away from negative words relative to healthy controls, the illness group did not significantly differ from healthy controls. Attention bias in K‐wire and illness groups was unrelated to later PTS symptoms.